(3LeGd GdESHhY dLeGd GdeTQhYs - (3Ydj Hf ehSi Hf LYaQ Hf WGhhS GdMSfj,J (B664 (3g` s ((3eMeO Hf eMeO Hf eMeO GdeOYh HaGVd Hf MSjfj s)
(3ChdgG (B:s
(3jbhd GdSjO CHhGdbGSe Ydi Hf ehSi GdWGhhSj GdMSjfj CMeO Gddg Ld LdGdg GdPj CjbX Phj GdSfiI ef Ggd GdhLhO HGdSfI GdaVd s
(3BNQgG (B:s
(3hTQafG HGdXaQ HeG gh Ld LdGdg Cgdg ef GdehGgH hgPG BNQ GdLRA GdQGHY ef cJGH egeGJ aj UdGM GdeJYHO hJJeGJ deUHGM GdeJgLO s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B248s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B365s
Keywords: (3GdJUha hGdBOGH GdTQYjIs